How do firms adjust their wage bill in Belgium? A decomposition along the intensive and extensive margins - Catherine Fuss (National Bank of Belgium, 2008)
This paper decomposes wage bill changes at the firm level into components due to wage changes, and components due to net flows of employment. The analysis relies on an administrative employer-employee dataset of individual annual earnings matched with firms' annual accounts for Belgium over the period 1997-2001. Results point to asymmetric behaviour depending on economic conditions. On average, wage bill contractions result essentially from employment cuts in spite of wage increases. Wage growth of job stayers is moderated but still positive; and wages of entrants compared with those of incumbents are no lower. The labour force cuts are achieved through both reduced entries and increased exits. Higher exits may be due to more layoffs, especially in smaller firms, and wider use of early retirement, especially in manufacturing. In addition, the paper points up the role of overtime hours, temporary unemployment and interim workers in adapting to short-run fluctuations.
Keywords: J30; J60; 330; wages; employment flows; matched employer-employee data; Arbeitskosten; Wirtschaftliche Anpassung; Arbeitsmobilität; Institutionelle Infrastruktur; Arbeitsmarkt; Belgien